2019
DOI: 10.3389/fphar.2019.01329
|View full text |Cite
|
Sign up to set email alerts
|

Qi-Li-Qiang-Xin Alleviates Isoproterenol-Induced Myocardial Injury by Inhibiting Excessive Autophagy via Activating AKT/mTOR Pathway

Abstract: Background: Apoptosis and autophagy are two important patterns of cell death in the process of heart failure. Qi-Li-Qiang-Xin (QLQX), a traditional Chinese medicine, has been frequently used in the treatment of chronic heart failure (CHF) in China. However, the potential effect of QLQX on autophagy has not been reported. In this study, we aimed to investigate whether QLQX alleviated isoproterenol (ISO)-induced myocardial injury through regulating autophagy. Methods: The rapid identification of chemical ingredi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 51 publications
3
33
0
Order By: Relevance
“…These changes verified the HF model in rats. Besides, heart rate and blood pressure were decreased while the plasma levels of BNP were significantly increased after ISO intervention (Wang et al, 2018;Fan et al, 2019). These results concur with previous studies.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…These changes verified the HF model in rats. Besides, heart rate and blood pressure were decreased while the plasma levels of BNP were significantly increased after ISO intervention (Wang et al, 2018;Fan et al, 2019). These results concur with previous studies.…”
Section: Discussionsupporting
confidence: 92%
“…The changes in rat associated with ISO-induced HF are similar to the pathological changes of myocardial tissue in the process of human heart failure. Hence ISO-induced HF in rats is an extensively applied model in experimental medical research (Fan et al, 2019). The heart failure model in our study was induced by subcutaneous injection with ISO.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results indicate that geraniol caused the activation of PI3k/Akt in a dose-dependent manner and suggest that it may have modulated the myocardial autophagy by this mechanism. In previous studies, numerous drugs have demonstrated cardioprotective activity through activation of the PI3K/Akt pathway; examples include Paeonol and danshensu [ 5 ], Vasicine [ 26 ], Qi-Li-Qiang-Xin (a traditional Chinese medication) [ 28 ], and Levosimendan [ 29 ]. Activation of the PI3K/Akt/mTOR pathway also protected against myocardial injury by diminishing oxidative stress, limiting the inflammatory cascade, and deterring apoptosis in vivo and in vitro [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…The high reproducibility of QLQX was clarified by a fingerprint analysis, which exhibited a high similarity of 10 batches ranging from 0.978 to 1.000 ( Zhang J. et al, 2013 ). Previous chemical analysis of QLQX, which was obtained from the same supplier and had the same batch number with QLQX in this study, identified the profile and concentrations of stable active ingredients ( Fan et al, 2019 ). Enalapril was obtained from Yangzijiang Pharmaceutical Group Jiangsu Pharmaceutical Co., Ltd. (Taizhou, Jiangsu, China) as the positive control.…”
Section: Methodsmentioning
confidence: 99%